Catheterization as a Treatment for Feline Lower Urinary Tract Disease (FLUTD) Case in K and P Clinic Surabaya - Annisha Permata Nurul Azhar; Lailia Dwi Kusuma Dewi; Palestin Palestin (Journal of Applied Veterinary Science And Technology, 2022)
Background: Feline Lower Urinary Tract Disease (FLUTD) is a case that occurs due to bladder and urethra dysfunction in cats. One of the symptoms of FLUTD is pollakiuria without polyuria, the presence of stranguria, and hematuria. Purpose: This case study aims to provide information regarding handling cases of Feline Lower Urinary Tract Disease (FLUTD) in 22 cats for one month at the K and P clinics in Surabaya. Case Analysis: Observation data presented descriptively were compared and discussed with supporting data. Conclusion: Inserting a catheter is the primary action that must be done if there is a blockage in the urethra.